An Innovative Model for Teaching Speaking Skills: Integrating Contextual and Cooperative Learning - M. Dzikrul Hakim Al Ghozali; Uril Bahruddin; Syuhadak (UIN Syekh Wasil Kediri, Indonesia, 2025)
This study addresses the lack of an effective learning model for speaking skills, which remains traditional and misaligned with students' competencies. Aiming to bridge this gap, the research designs a speaking skill teaching model grounded in cooperative and contextual learning, then examines its validity for Arabic Language Education students at KH. Abdul Wahab Hasbullah University (UNWAHA) Jombang. Adopting Borg and Gall’s research and development (R&D) approach, this study combines qualitative and design-based methodologies. Data were collected through classroom observations, interviews, and questionnaires, then analyzed using both qualitative and quantitative techniques. Key findings include: (1) the speaking skill teaching model developed on the basis of cooperative and contextual learning was designed using the Borg and Gall steps. The teaching model guide consists of three main stages of educational activities, namely introductory activities, core activities, and concluding activities, and includes educational content, technical specifications, and implementation steps. (2) Validation by experts confirmed the model’s high usability. The teaching model received a 90% score (“excellent”) from instructional design experts, while material experts rated the accompanying resources at 89% (“excellent”), reflecting robust readiness for classroom implementation. These results demonstrate that the cooperative and contextual learning-based model offers a theoretically sound and empirically validated approach to enhancing speaking skills in Arabic language education. The study underscores the importance of modernizing pedagogical frameworks to better align with learner needs.